The Capgras Shift - Vaknin, Samuel, 1961- (Salt Lake City, UT : Project Gutenberg, 2008)
"The Capgras Shift" by Samuel Vaknin is a psychological drama written in the early 21st century. The book explores themes of mental illness, specifically delusions involving the Capgras Syndrome, where individuals believe that their loved ones have been replaced by impostors. Through its narrative, the book delves into the complexities of human relationships, identity, and the profound impact of grief and loss. In the story, the protagonist is a therapist starting anew in a desolate setting following personal setbacks. He encounters Isabel, an elderly woman who believes her family has been replaced by fraudulent doubles, a manifestation of her emotional turmoil over the loss of her home and loved ones due to a government project. As their sessions progress, the therapist becomes increasingly entangled in Isabel's world and her concerns about identity and trust. The narrative builds tension as Isabel hosts a dinner for her family, where she questions their authenticity, leading to a web of psychological manipulation and self-doubt that unveils deeper themes regarding reality, perception, and the fragility of the human mind. (This is an automatically generated summary.)
Release date is 2008-01-02
Keywords: Short stories; Psychological fiction; Capgras syndrome -- Fiction